?ESTIMATION OF LEAF DAMAGE OF BANANA AFFECTED BY BANANA LEAF AND FRUIT BEETLE, NODOSTOMA VIRIDIPENNIS MOST. (COLEOPTERA: EUMOLPIDAE) IN BANGLADESH (Biological Sciences - PJSIR, 2003)
The study was made to evaluate the nature, extent of damage and susceptibility of banana leaf (furled leaf, freshly open leaf and mature leaf) affected by leaf and fruit beetle, Nodostoma viridipennis Most. in an orchard in Bangladesh Agricultural University, Mymensingh from October, 1997 to October, 1998. The beetle produced damage symptom with the sign of scars and dried feeding areas on banana leaf. The greatest damage was done to furled leaf bearing 69.8 scars which was 1.3 and 2.0 times higher than freshly open and mature leaf, respectively. The furled leaf being suitable feeding was more susceptible than other categories of leaf and seemed to be the target of colonization of leaf and fruit beetle in the orchard. The growth and development of banana leaf was affected by the damage of N. viridipennis. There was significant reduction in size of infested furled leaf. The difference of leaf size in case of freshly open and mature leaf was not so marked.